A Review on the Relationship between Aspirin and Bone Health. (9th January 2017) - Chin, Kok-Yong
Abstract : Aspirin is a cyclooxygenase inhibitor commonly used in primary prevention of cardiovascular diseases and cancers. Its users are elderly population susceptible to osteoporosis. It also inhibits the synthesis of prostaglandin E2 essential in bone remodeling. This prompts the question whether it can influence bone health among users. This review aimed to summarize the current literature on the use of aspirin on bone health. A literature search on experimental and clinical evidence on the effects of aspirin on bone health was performed using major scientific databases. In vitro studies showed that aspirin could enhance the survival of bone marrow mesenchymal stem cells, the progenitors of osteoblasts, and stimulate the differentiation of preosteoblasts. Aspirin also inhibited the nuclear factor kappa-B (NF κ B) pathway and decreased the expression of receptor activator of NF κ B ligand, thus suppressing the formation of osteoclast. Aspirin could prevent bone loss in animal models of osteoporosis. Despite a positive effect on bone mineral density, the limited human epidemiological studies revealed that aspirin could not reduce fracture risk. A study even suggested that the use of aspirin increased fracture risk. As a conclusion, aspirin may increase bone mineral density but its effect on fracture prevention is inconclusive. More data are needed to determine the effects of aspirin and bone health in human.